Citrullinemia in a newborn: a case report - G. S. Golosnaya; T. N. Belousova; M. Yu. Novikov; N. Yu. Knyazeva; D. Yu. Podkopaev; E. G. Trifonova; A. I. Makulova; Ya. Ya. Ginen; Z. A. Kozheurova; D. A. Kholichev; D. A. Politov; P. V. Baranova; et al. (Русский журнал детской неврологии, 2022)
Inherited metabolic disorders have a specific place among cases of sudden deterioration of the newborn’s condition. Therapies have been developed for some of these disorders. Accurate verification of the diagnosis is extremely important for choosing an optimal treatment strategy. However, treatment is not always successful due to the rapid progression of symptoms. We report a case of citrullinemia diagnosed in a newborn in Vidnoye Perinatal Center.